Flexural strength of recycled concrete aggregate and mild steel rebar - Muhamad Rahimi Wan Yaakub (School of Environmental Engineering, University Malaysia Perlis, 2012)
This study was conducted to determine curve reinforced concrete that recycled concrete aggregate (rac) . Usage recycled concrete aggregate (rca) in this study to change stone volume diffuse use percentage ratio that is different as much as 0 % (control concrete), 30 % and 50 %. This study show sample nature decision in 28 days.Specimen used in this study use mold 200 mm x 300 mm x 1200 mm. Outcome of experiment compared to plain concrete sample with features that is same. Decision acquired shows that recycled concrete aggregate 0 % have curve strength that is highest compared to sample that in plus with 30 % and 50 % concrete recycling . Concrete mix curve strength recycling as much as 50 % is lowest. For strain strength beam that highest is with mixture 0% concrete recycling . It because, strain still occur in burden 66.67 kN in impose on beam. For sample beam with concrete mix recycling 30 % and 50 %, strain only occurred until 40 kN and 33.33 kN burden in impose before sample occur failure.